Strategies for Jambi Culinary MSMEs to Survive in the Digital Era: The Influence of Financial Literacy and E-Commerce - Heriyani, Heriyani; Murnidayanti, Scheilla Aprilia; Putra, Dios Nugraha; Prasetio, Primadi; Dahlia, Dahlia (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to determine the extent to which financial literacy and e-commerce utilization influence the sustainability of culinary MSMEs in Jambi City. The research question addressed is whether financial literacy and e-commerce individually and jointly have a significant impact on business sustainability. A quantitative approach was employed through survey methods involving 100 culinary MSME respondents. Data were analyzed using multiple linear regression, preceded by validity, reliability, and classical assumption tests to ensure data quality. The results indicate that financial literacy and E-Commerce has a positive and significant effect on MSME sustainability. These findings highlight the crucial role of improving financial literacy and adopting digital technology in supporting the growth and resilience of MSMEs in the era of digital transformation. The impact of this research is expected to provide a basis for the formulation of MSME development strategies by local governments and related institutions, as well as to encourage business actors to become more adaptive to technological changes and effective financial management.